Relative efficiency of split-marker versus double-crossover replacement protocols for production of deletion mutants in strain PH-1 of Fusarium graminearum - Sladana Bec; Gabdiel E. Yulfo-Soto; Lisa J. Vaillancourt (Fungal Genetics Reports, 2021)
The split-marker (SM) protocol has become a popular method for production of knockout mutations in fungi. We used Southern hybridization to compare the performance and efficiency of the SM protocol with the more traditional double-crossover intact marker (IM) method for creating deletions of the mating type genes in Fusarium graminearum. Both methods successfully produced knockouts at a rate of between 24 and 75%: the SM method produced mutants more efficiently for larger constructs (>1 kb), but it was similar to IM for a smaller construct that was 865 bp. Both methods also produced strains with additional ectopic integrations at a similar rate of approximately 10%, but on average the SM produced a higher number of independent integrations in those strains. Ectopic integrations produce off-site mutations, and strains with multiple integrations are less desirable since it is more difficult to remove them by backcrossing. Southern hybridizations will be generally superior to PCR to identify strains with fewer ectopic integrations for experimental purposes.
Keywords: Transformation; Gene knockouts; Fungal mating type genes